Pengaruh Suku Bunga, Nilai Tukar Uang, dan Inflasi Terhadap Harga Saham ( Studi kasus pada perusahaan Bank yang terdaftar di BEI periode 2010-2012 ) - Syahid, Hertasnim; Mardiati, Endang (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to determine the influence of fundamental variables consisting of interest rate, exchange rate, and inflation on stock prices , as well as identify and analyze the dominant variable affecting on stock price in the banks companies period 2010-2012 who listed in Indonesia Stock Exchange. This study also explains the existence of influence between the dependent and independent variables. The population of this study were 31 banks listed companies in Indonesia Stock Exchange. For sampling that meet specified criteria, then obtained a sample of 15 bank companies. Based on the population and the sample, then used Â multiple regression method to analyzed. The results using multiple linear regression analysis showed Interest Rates, Exchange Rates, Inflation affects 41.3 % of the stock price, while the remaining 58.7 % is influenced by other variables that are not included in this research model. Conclusion, it can be concluded that the three independent variables, consist of interest rates, exchange rates, and inflation have an influence on company's stock price of the bank. Variable Value Exchange Rate is a variable that has dominant influence on stock prices of banks companies listed in Indonesia Stock Exchange . Keywords : Interest Rates, Exchange Rates Money , Inflation, Stock Price.